(untitled) (El-Wahat Journal for Research and Studies, 2021)
The Universality Of The Arabic Language Has Many Manifestations Such As Its Inscription As Many Languages, From Within Its Family And Out Of It, Used The Arabic Letter Script And Others Relate To Its Grammar And System Of Permutation. Abu Hayan Used Arabic Grammar To Examine Turkish Vocabulary And Its Grammar. Many Other Grammarians Also Made Use Of Its System Of Permutation To Study The Hebrew Language; Some Of These Properties Exist In The Roots Of Its Lexicon. Thus Scholars Of Semitic Languages Still Make References To Arabic. Some Relate To Its Grammar And Factor Theory As Many European Scholars Borrowed It To Become Nicknamed Dependency Grammar. Then It Was Used By Noam Chomsky In His Transformational Generative Grammar. This Research Will Reveal All Aspects, Albeit Briefly, That Indicates The Universality Of The Arabic Language, Both In The Past And Now. This Pushes Us Further To Preserve Our Language, Its Originality, Accuracy And Depth Of Its System. Indeed, Arabic Is Still Rich Due To Its Inherent Potentials Which Are Rarely To Be Found In Other Languages. Key Words- Universality Of Arabic, Word Structures, Inscription, Factor Theory, Grammar Dependency.